Valorization of bamboo shoot shell waste for the coproduction of fermentable sugars and xylooligosaccharides - Wang, Qiyao; Su, Yan; Gu, Yang; Lai, Chenhuan; Ling, Zhe; Yong, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
In this work, hydrothermal pretreatment (autohydrolysis) was coupled with endo-xylanase enzymatic hydrolysis to treat bamboo shoot shell (BSS) to produce of glucose and valuable xylooligosaccharides (XOS) rich in xylobiose (X2) and xylotriose (X3). The results showed that the enzymatic hydrolysis of pretreated BSS residue reached to 88.4%with the PEG addition during hydrolysis process. To obtain more portions of valuable X2-X3 in XOS, endo-xylanase was used to hydrolyze the XOS in the prehydrolysate. After hydrolysate (170 °C, 50 min) hydrolysis by endo-xylanase, the yield of XOS reached 25.6%, which contained X2-X3 amount of 76.7%. Moreover, the fermentation inhibitors in the prehydrolysate were found at low concentrations (formic acid 0.7 g/L, acetic acid 2.6 g/L, furfural 0.7 g/L). Based on mass balance, 32.1 g of glucose and 6.6 g of XOS (X2-X3 with 5.1 g) could be produced from 100.0 g of BSS by the coupled technology. The results indicated that BSS could be an economical feedstock for the production of glucose and XOS.